Penerapan Keadilan Restoratif Dalam Tindak Pidana Ringan - Kurnia, Evita Ayu; Rosando , Abraham Ferry (Harmonization : Jurnal Ilmu Sosial, Ilmu Hukum, dan Ilmu Ekonomi, 2023)
Criminal cases can get addressed by the judicial structure as well as different dispute resolution procedures. Because litigation is the method of resolution of conflicts used most frequently hired, little-known crimes have been settled through litigation in Indonesia. In the real world, how these cases get resolved by means of the justice system may end up resulting in novel issues including retaliatory punishment patterns, that give rise to an overabundance of cases, neglect to feed the rights of victims, overstatements of the detrimental impact of crime on society, and an unwillingness to maintain basic judicial principles. It is envisioned that with the establishment of fresh approaches based on the principle of restorative justice, a justice system that reflects a sense of justice will benefit the community in accordance with Pancasila. The present piece is an account of normative research, consisting involved identifying a framework for law, principles of guidance, and legal doctrines to deal with matters of law. Therefore, it might be derived that the principle of restorative justice affords perpetrators with legal protection provided cases go away using non-litigation channels, avoiding societal shame. The recovery of the situation as had occurred before, the return of what was stolen to the koban, the restitution of expenses for losses paid for, including the repair of the damage resulting from illicit behavior are several instances of legal protection for victims. consequently is projected that the idea of restorative justice will eventually be able to provide both camps a solution.